Case Report: Minimally invasive repair of a traumatic abdominal wall hernia in a child with a fascial closure device - Lu, Huiyu; Zhang, Zemin; Chao, Jun; Zhang, Chuanguang; Zhang, Guoqing; Tao, Shujie; Yan, Qingtao (Frontiers in Surgery, 2024)
Abdominal traumas is common in our daily life, but traumatic abdominal wall hernia (TAWH) in children is rare. TAWH is caused by a huge external force that leads to subcutaneous muscle and fascia rupture, but the skin is intact. As abdominal pressure increases, the abdominal contents protrude and form a lump. It is highly susceptible to missed diagnosis because of other severe injuries. We report a two years old male child with TAWH who developed a prominent subcutaneous mass on the right side of his abdomen after abdominal trauma, and the size of the mass changed significantly with abdominal pressure and crying. In this case, we used a new approach of laparoscopic suture repair technique with the assistance of a fascial closure device to repair it, and achieved good results. We found that this method has the advantages of minimally invasive, fast recovery and no visible surgical incisions. There was no recurrence after 8 months of follow-up.